2011
DOI: 10.7150/jca.2.538
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Melanoma in the Elderly: Different Regional Disease and Poorer Prognosis

Abstract: Purpose: Age is a poor prognostic factor in melanoma patients. Elderly melanoma patients have a different presentation and clinical course than younger patients. We evaluated the impact of age ≥70 years (yrs) on the diagnosis and natural history of melanoma.Methods: Retrospective review of 610 patients with malignant melanoma entered into a prospective sentinel lymph node (SLN) database, treated from June 1997 to June 2010. Disease characteristics and clinical outcomes were compared between patients ≥70 yrs vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
86
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 39 publications
14
86
4
1
Order By: Relevance
“…16 In particular, older males had a 157% increase in melanoma mortality between 1969 and 1999. [2][3] In one retrospective analysis, 17 overall mortality and disease-specific mortality at 5 y was statistically inferior in patients 70 y of age. Advancing age is associated with more aggressive biologic behavior, as well as a lower percentage of patients with BRAF mutation, especially V600E BRAF mutation, which is the most sensitive to targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In particular, older males had a 157% increase in melanoma mortality between 1969 and 1999. [2][3] In one retrospective analysis, 17 overall mortality and disease-specific mortality at 5 y was statistically inferior in patients 70 y of age. Advancing age is associated with more aggressive biologic behavior, as well as a lower percentage of patients with BRAF mutation, especially V600E BRAF mutation, which is the most sensitive to targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, increasing age was significantly associated with poor prognostic markers of Breslow thickness, ulceration, and male gender. [17][18][19][20][21] Moreover, with the anticipated growth in the elderly population, the number of older melanoma patients seeking treatment is predicted to lead to increased healthcare costs and utilization of resources, 22 underscoring the importance of optimal management of melanoma in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] The risk associated with sun exposure and multiple naevi, for example, are controversial. 8,9 Traditional prognostic factors for cutaneous MM include thickness, ulceration, mitoses/mm 2 , clinical stage, anatomic location, sex and age, 10 and although some pathologic features were previously linked to lower disease specific survival rates, 4,5,7,10 some associations remain uncertain in older patients. 10 In accordance to our findings, several studies suggested that melanoma is more common in older men; 3,4,6-8,10 they have focused on histologic features and/or survival, and few evaluated risk factors for melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Some melanoma features seem to differ according to age, including prognosis markers and risk factors. 3,[5][6][7] This case series aimed to identify clinicopathological differences of MM between older and younger patients.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant melanoma is the most aggressive type of skin cancer, with rapidly increasing incidence worldwide [1][2][3]. Despite previous intensive research to advance our understanding of melanoma progression, therapeutic options remain limited, and melanoma is mainly cured surgically [4,5].…”
Section: Introductionmentioning
confidence: 99%